Differential accumulation of soluble proteins in roots of metallicolous and nonmetallicolous populations of Agrostis capillaris L. exposed to Cu. Issue 15 (16th June 2014) - Hego, Elena; Bes, Clémence M.; Bedon, Frank; Palagi, Patricia M.; Chaumeil, Philippe; Barré, Aurélien; Claverol, Stéphane; Dupuy, Jean‐William; Bonneu, Marc; Lalanne, Céline; Plomion, Christophe; Mench, Michel
<x xml:space="preserve">Abstract</x> Differential expression of soluble proteins was explored in roots of metallicolous (M) and non‐M (NM) plants of Agrostis capillaris L. exposed to increasing Cu to partially identify molecular mechanisms underlying higher Cu tolerance in M plants. Plants were cultivated for 2 months on perlite with a CuSO4 (1–30 μM) spiked‐nutrient solution. Soluble proteins extracted by the trichloroacetic acid/acetone procedure were separated with 2DE (linear 4–7 pH gradient). After Coomassie Blue staining and image analysis, 19 proteins differentially expressed were identified using LC‐MS/MS and Expressed Sequence Tag (ESTs) databases. At supra‐optimal Cu exposure (15–30 μM), glycolysis was likely altered in NM roots with increased production of glycerone‐P and methylglyoxal based on overexpression of triosephosphate isomerase and fructose bisphosphate aldolase. Changes in tubulins and higher expressions of 5‐methyltetrahydropteroyltriglutamatehomocysteine methyltransferase and S‐adenosylmethionine synthase underpinned impacts on the cytoskeleton and stimulation of ethylene metabolism. Increased l‐methionine and S‐adenosylmethionine amounts may also facilitate production of nicotianamine, which complexes Cu, and of l‐cysteine, needed for metallothioneins and GSH. In M roots, the increase of [Cu/Zn] superoxide dismutase suggested a better detoxification of superoxide, when Cu exposure rose. Higher Cu‐tolerance of M plants would rather result from simultaneous cooperation of various processes than from a specific mechanism.